The relationship between hepatic high FIB-4 score and COVID-19 pneumonia - Demir, Esra; Erol, Vedat Buğra; Olmuşçelik, Oktay; Koryürek, Özgül M.; Tabak, Ömür; Demir, Bülent (Clinical Laboratory Publication, 2022)
Background: We aimed to compare the level of hepatic FIB-4 scores between COVID-19 patients who had pneu-monia and COVID-19 patients who had no pneumonia in an attempt to develop a risk assessment after the treat-ment and recovery of active COVID-19 infection. Methods: The study included 80 patients who were consecutively selected and admitted to an internal medicine outpatient clinic for a control examination after COVID-19 infection. Chest tomography was performed on all pa-tients during the COVID-19 infection. Patients were divided into two groups as those with and without lung in-volvement on CT. COVID-19 infection was diagnosed using real-time reverse transcription-polymerase chain re-action (RT-PCR). The hepatic fibrosis 4 (FIB-4) index score was calculated for each patient. The statistical ana-lyses were performed using Student's t-test and chi-squared tests. Results: We found that the increased hepatic FIB-4 index score in patients with pneumonia group was statistically significant compared to the control group (p < 0.001). The regression analysis showed that the hepatic FIB-4 index has significant prognostic efficiencies in both uni-and multivariate models (p < 0.05). Conclusions: The hepatic FIB-4 index appears to be a simple parameter with a good prognostic value in patients with COVID-19 infection.
Keywords: Coronavirus Infections; Liver Fibrosis; Pneumonia; Prognostic Factors